FAKTOR YANG MEMPENGARUHI SISWA DALAM PEMILIHAN PROGRAM KEAHLIAN DENGAN MENGGUNAKAN ANALISIS KORESPONDENSI - Ahmad Labib Al Jauzi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
The research aims to know the data analysis with using simple correspondence analysis methods (simple correspondence analysis) then used to analyze the correlation between parental income, parental occupation, interests and talents of students to the factors influencing the selection of students in vocational skills program in Sasmita Jaya 1. Based on the research results, there is a relationship between these factors with the membership program selection factors can be indicated by the value of each chi-square of the four factors is more than the value of the alpha chi squared 33.853; 41.520; 27.696 and 38.080. Of the four plots correspondence shows. Students who choose Accounting skills programs has a talent in the field of Logical mathematically, a good interest and have parents who work as employees. Students who choose Marketing skills programs has a talent in the field of Linguistics, interest was good and had parents who worked as others. Students who choose programs in Administrative skills has a talent in the field of Linguistics, considerable interest and have parents who work as entrepreneurs. Students who choose the program Multimedia has a talent in the field of Visual Spatial, interest was very good and had parents who worked as an entrepreneur. Students who choose the program expertise Pharmacy has a talent in the field of Physical kinesthetic, considerable interest and have parents who work as civil servants